The regular analyses of flora of Gimry and Salatau chains (the East Caucasus) - Z. I. Soltanmuradova; M. N. Balaeva (Юг России: экология, развитие)
Regarded, that the plants‘s cover in Daghestan is well studied. However, flora in some regions, such as Gimrinskiy and Salatau chains are not investigated completely. The aim of analyses of flora is revealing and comparatively appraising the flora indicators, focusing on their systematic geographical, ecological and other characteristics.